Assessment of Gamma Ray Shielding Properties for Skin - MALİDARRE, Roya Boodaghi; OZAN TEKİN, Huseyin; GUNOGLU, Kadir; AKYILDIRIM, Hakan (International Journal of Computational and Experimental Science and Engineering, 2023)
Gamma ray is an energetic radiation type that can ionize and thus damage living cells as it slows down and transfers its energy to cells. Because of this harmful effect cell should be protected. Besides developing new alternative to lead and lead based materials, it should be interesting to obtain shielding properties of skin. This paper presents a results on the shielding properties of skin.